A Rare Case of Congenital Syphilis Presented with Pneumonia alba - Vinitha Arjula; Mounica Adari; Sudharshan Raj Chitgupikar (Pediatric Infectious Disease)
Congenital syphilis is an infectious disease primarily caused by the hematogenous transmission of Treponema pallidum, a spirochete bacterium, from an infected mother to the fetus through the placenta during pregnancy. In the present era, congenital syphilis manifests as prematurity intrauterine growth retardation (IUGR) and can develop as acute systemic illness (Pneumonia alba, nonimmune hydrops), bone deformities, developmental disabilities, blindness, or deafness immediately or later in life. We report an infant diagnosed with congenital syphilis with IUGR and pneumonia at birth. This case reveals that there is an incidence of missed prevention and the importance of awareness and maternal screening for syphilis in the antenatal period.